2020
DOI: 10.1186/s12917-020-02571-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heel elevation on breakover phase in horses with laminitis

Abstract: Background In a laminitic horse, the maximal loading of the toe region occurs during the breakover phase. To date, no kinetic data demonstrates the effect of supportive orthopaedic therapy in horses with laminitis on breakover phase. Thus, the purpose of this study was to examine the effect of heel elevation on the breakover phase. Eight horses with acute laminitis treated medically as well as with application of a hoof cast with heel wedge (HCHW) were included in this study. Immediately following cessation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our final hypothesis stating that the maximum effect of diagnostic anaesthesia occurs during midstance has to be rejected, as we observed the maximum increase in vertical force on the anaesthetised limb during breakover. This result emphasises the meaning of this phase for equine locomotion and compensation mechanisms of painful processes in the limb [ 12 , 20 , 34 ] so that the loss of sensory feedback after diagnostic anaesthesia [ 35 ] might become more obvious during this part of the stance phase.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our final hypothesis stating that the maximum effect of diagnostic anaesthesia occurs during midstance has to be rejected, as we observed the maximum increase in vertical force on the anaesthetised limb during breakover. This result emphasises the meaning of this phase for equine locomotion and compensation mechanisms of painful processes in the limb [ 12 , 20 , 34 ] so that the loss of sensory feedback after diagnostic anaesthesia [ 35 ] might become more obvious during this part of the stance phase.…”
Section: Discussionmentioning
confidence: 97%
“…In a former study, it was reported that the Hoof™ System is not reliable compared to a force platform when being fixed with an equine hoof boot [ 22 ]. The reliability of mounting the sensor foils with adhesive tape was not evaluated in the current or former studies [ 18 , 19 , 21 , 34 ], which may have had an influence on the results. Another study could show reliability within but not between sessions when the sensor foils were attached with a glue-on shoe [ 38 ].…”
Section: Discussionmentioning
confidence: 99%